Benefits and adverse effects of endocrine therapy - Colleoni, M. (Oxford University Press, 2010)
Endocrine-responsive tumors that are small and without nodal involvement (i.e. tumors classified as pT1 pN0) are a heterogeneous group of tumors that are associated with a low risk of relapse in the majority of the cases. Therefore, the costs and benefits of adjuvant endocrine therapy should be carefully considered within this subgroup of patients. Treatment decisions should take into consideration co-morbidities as well as the presence of other classical risk factors such as HER2 overexpression or extensive peritumoral vascular invasion. Tamoxifen or tamoxifen plus ovarian function suppression should be considered as proper endocrine therapies in premenopausal patients. Ovarian function suppression alone or ovarian ablation might also be considered adequate in selected patients (e.g. very low-risk patients, in the presence of co-morbidities or patient preference). An aromatase inhibitor should form part of standard endocrine therapy for most postmenopausal women with receptor-positive breast cancer, although patients at low risk or with co-morbid musculoskeletal or cardiovascular risk factors may be considered suitable for tamoxifen alone. Tailored endocrine treatments should be considered in patients with endocrine-responsive tumors classified as pT1 pN0. Issues focusing on safety, quality of life and subjective side effects should be routinely discussed.